The effect of uncertainty on foreign direct investment: The case of Mexico - López Noria, Gabriela; Zamudio Fernández, Juan José (Estudios Económicos de El Colegio de México, 2018)
This paper investigates the effect of uncertainty on FDI flows into the Mexican manufacturing sector during the period 2007-2015. Using a panel of manufacturing subsectors, we estimate a model by System GMM that includes domestic and external factors, as well as idiosyncratic and aggregate uncertainty measures as explicative variables. We also performsome simulations to assess the size of the uncertainty effect on FDI flows. The main results show that uncertainty discourages FDI flows into the Mexican manufacturing sector during this period. We also find that idiosyncratic uncertainty measures are more important in explaining FDI flows than aggregate uncertainty measures.